2019
DOI: 10.1016/j.dld.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Which heart rate variability index is an independent predictor of mortality in cirrhosis?

Abstract: Background: Liver cirrhosis is associated with reduced heart rate variability (HRV), which indicates impaired integrity of cardiovascular control in this patient population. There are several different indices for HRV quantification. The present study was designed to: 1) determine which of the HRV indices is best at predicting mortality in patients with cirrhosis; 2) verify if such ability to predict mortality is independent of the severity of hepatic failure. Methods: Ten minutes electrocardiogram was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 45 publications
7
41
0
Order By: Relevance
“…Further models using a network approach should include more physiological data, such as heart rate variability and temperature variability indices. Reduced heart rate variability and body temperature variability are known to be inversely associated with increased mortality in cirrhosis patients, where their prognostic value is independent of MELD or Pugh scores (Mani et al, 2009;Bhogal et al, 2019;Bottaro et al, 2020). In a subset of patients investigated, the uncoupling of the autonomic nervous system and cardiovascular system was found to be associated with mortality in liver cirrhosis patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Further models using a network approach should include more physiological data, such as heart rate variability and temperature variability indices. Reduced heart rate variability and body temperature variability are known to be inversely associated with increased mortality in cirrhosis patients, where their prognostic value is independent of MELD or Pugh scores (Mani et al, 2009;Bhogal et al, 2019;Bottaro et al, 2020). In a subset of patients investigated, the uncoupling of the autonomic nervous system and cardiovascular system was found to be associated with mortality in liver cirrhosis patients.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have suggested the addition of further predictive components such as in the proposal of the MELD-Plus score (Kartoun et al, 2017), while other studies have identified physiomarkers independent to the MELD score in mortality prediction. Montagnese et al (2015) has shown that the addition of an EEG-based hepatic encephalopathy index to MELD improves prognostic accuracy, while Bhogal et al (2019) has defined two heart rate variability indices that predict mortality in cirrhosis patients independently to MELD. The liver remains the primary site of initial pathophysiology development in cirrhosis, and though it is important to include specific liver biomarkers in survivor analysis, the progression of cirrhosis and its downstream effects means that inclusion of involved organ system biomarkers is paramount to reflecting the true complexity of liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is not known whether temperature variability analysis has a prognostic value in the context of cirrhosis. Recent studies have shown that physiological markers such as heart rate variability (HRV) predict mortality in patients with cirrhosis, independently of other indices of liver failure such as the Child-Pugh and MELD (Model for End-Stage Liver Disease) scores (Bhogal et al, 2019;Satti et al, 2019). It appears that systemic inflammation is involved in the pathogenesis of poor prognosis in cirrhosis (Clària et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that systemic inflammation is involved in the pathogenesis of poor prognosis in cirrhosis (Clària et al, 2016). Systemic inflammation is linked with reduced HRV (Bhogal et al, 2019;Haddadian et al, 2013) and altered body temperature dynamics in chronic liver failure (Mani et al, 2018), so it is plausible to assess these physio-markers in prediction of poor prognosis in cirrhosis.…”
Section: Introductionmentioning
confidence: 99%